Statistical Study of Cancer in Diyala Provenance - Salam Hasoon Mohammad ,; Ruaa A Salman (Diyala Journal of Medicine, 2022)
Background: Malignant neoplasms are a group of illnesses involving altered cell proliferation with the ability to invade or metastasize to other sites of the body.  Not all neoplasms are malignant; benign neoplasms do not metastasize to other parts of the body.